A REVIEW ON DEVELOPMENT AND VALIDATION OF STABILITY INDICATING HPLC METHODS FOR ANALYSIS OF ACIDIC DRUGS - RODE, DEVYANI M.; RAO, NUTAN N. (International Journal of Current Pharmaceutical Research, 2019)
High-performance liquid chromatography is one of the fastest, safest and precise technology used for determination and separation of pharmaceutical drugs, impurities and biological samples. High-performance liquid chromatography is versatile and it takes less time for quantification of drugs as compared to old liquid chromatography techniques. This article reviews stability indicating HPLC method developed and validated for acidic drugs and their degradation studies.